Role of Vestibular Suppressants (B. Histine, Cinnarizine, Meclizine) after Successful Epley’s Maneuvers in Benign Paroxysmal Positional Vertigo - Muhammed Tahir, Ghulam Fareed, Abdul Hakim, Asad Ali, Haitham Akaash, Arslan Akhtar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Benign positional paroxysmal vertigo (BPPV) is one of the most prevalent causes of dizziness, affecting between 11 and 64 people per 100,000 each year and 2.4% of the population overall. Vestibular suppressants have been shown in recent studies to be effective in reducing residual symptoms after a successful Epley’s maneuvers, however to the best of our knowledge, very few research have analyzed the features of residual symptoms in BPPV patients following Epley’s maneuvers. There has been no definitive research on what causes symptoms duration, canal involvement, cumulative successful ratee, residual symptoms and dysregulation are among possibilities put up to explain the phenomenon. Objective: This research focused on role of vestibular suppressants including B.histine, cinnarizine, and meclizine after successful Epley’s maneuvers in benign paroxysmal positional vertigo Study Design: Cross-sectional study Study Setting: The study was conducted at department of ENT CMH, Multan from 01 January 2022 to 30th October 2022. Methodology: Total 135 patients were divided into two groups. In group A 60 patients were taking vestibular suppressants and in group B 75 patients were not taking any drugs, both groups had successful Epley’s maneuvers in benign paroxysmal positional vertigo Patients were considered for inclusion if they had idiopathic BPPV. A single doctor made the BPPV diagnosis after examining a patient’s history and doing a hall pike test. The patients’ symptoms duration, canal, cumulative success rate and residual symptoms were measured immediately after treatment, and two weeks. The statistical analysis was done by using SPSS version 20. Results: In group A out of which 24 were taking B.histine, 26 were taking cinnarizine, and 25 were taking meclizine as vestibular suppressants. In group B, 75 participants after successful Epley’s maneuver were not taking any vestibular suppressants. In this study there is 29 males and 31 females in group A and 37 males and 38 females in group B. Interestingly, the success rate with one treatment cycle was higher in the group A (p = 0.001). Further analysis of outcomes showed the residual symptoms in patients with a short (≤4 days) symptom duration revealed a correlation with the successful Epley’s maneuver in group A. Practical Implication: Vestibular suppressants have been standard practice in most hospitals for the treatment of severe vertigo for decades. Vertigo caused by vestibular imbalance can be treated with vestibular suppressants. When Epley’s Maneuvers have been performed successfully in patients with BPPV, the efficacy of Vestibular Suppressants (B.Histine, Cinnarizine, Meclizine) has not been conclusively established. So, their role must be studied. Conclusion: Finally, we found that patients who used anti-vestibular suppression medication following an Epley’s technique for treating and controlling BPPV symptoms fared better than those who did not. We advise the Epley method for BPPV therapy with the maintenance of suppressants for the better management. Keywords: B.histine, cinnarizine, meclizine, Epley’s maneuvers, paroxysmal positional virtigo